2015
DOI: 10.1016/j.parkreldis.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressive treatments for Parkinson's disease: A systematic review and meta-analysis

Abstract: This meta-analysis demonstrates that pharmacologic treatment with antidepressant medications, specifically the selective serotonin reuptake inhibitors (SSRIs), and behavioral interventions (CBT) significantly improved depression among Parkinson's disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 67 publications
(97 reference statements)
4
71
1
4
Order By: Relevance
“…Besides, different studies could draw contradictive conclusions. For example, Bomasang-Layno et al [60] concluded from 13 trials that SSRI could significantly improve depression of PD with high efficacy, which is consistence with our results. Yet Troeung et al [61] observed in their study that the pooled effects of antidepressive medication in PD were insignificant, which involved 9 clinical trials.…”
Section: Discussionsupporting
confidence: 92%
“…Besides, different studies could draw contradictive conclusions. For example, Bomasang-Layno et al [60] concluded from 13 trials that SSRI could significantly improve depression of PD with high efficacy, which is consistence with our results. Yet Troeung et al [61] observed in their study that the pooled effects of antidepressive medication in PD were insignificant, which involved 9 clinical trials.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the mechanism of ECT in treating PD-related depression may be a result of increased dopamine receptor binding caused by electroconvulsive stimulation in brain regions implicated in depression such as the nucleus accumbens (24,25). It is likely that the anti-depressant mechanism of ECT is not completely unique in PD patients (26). …”
Section: Discussionmentioning
confidence: 99%
“…This includes depression in PD (Bomasang-layno et al, 2015; Jaunarajs et al, 2011; Lewitt, 2012; Troeung et al, 2013). Degeneration of the locus coeruleus, the source of noradrenergic projection neurons in the brain, occurs in PD relatively early in Braak Stage 2 (Table 1) (Goedert et al, 2013).…”
Section: Parkinson’s Diseasementioning
confidence: 99%